Analysis of Automated PCB Test Station dashboard With Livewire by New Wave Concept - Muhammad Fachri Ramadhan; Zidni Ma’ruf; Indra Brucman; Raditiawan (PT. Hasba Edukasi Mandiri, 2026)
This research aimed to establish whether an automated Printed Circuit Board (PCB)-Tester, was developed using the New Wave Concepts, Livewire Simulation Environment, performs efficiently and technically. The quantitative approach used a comparative experimental design with five different circuits including A 4-diode power supply, a bridge rectifier power supply with 4 diodes, a NOT gate, an AND gate, and an OR gate. Each circuit was compared under two conditions (control & experimental) as well as between manual & automated designs, where all of the above circuits would be tested resulting in reliable data after at least five repetitions. The findings of this research indicate that PCBs manufactured with the New Wave Concept are more efficient for circuit design; on average the amount of time required to design a PCB using automated circuit designs was over 60% less than the time needed to design manually. Furthermore, in addition to improving efficiency, the automated circuit testing system also achieved high levels of reliability, achieving an average voltage accuracy greater than 98% and identifying potential wiring issues prior to actual physical manufacture, which supports the claim that Livewire's automated features are an effective means of performing pre-production diagnostics on PCBs, in addition to reducing both the risk of human error and reducing the total cost to manufacture and/or produce electronic components.